2008
DOI: 10.1155/2009/341275
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Resistance of Diarrheagenic Escherichia coli and Shigella Species Associated with Acute Diarrhea in Tehran, Iran

Abstract: A study was performed to determine the prevalence and antimicrobial resistance of Shigella species and diarrheagenic Escherichia coli isolates cultured from patients with acute diarrhea in Tehran, Iran. Between May 2003 and May 2005, 1120 diarrheal specimens were collected and assayed for bacterial enteropathogens by conventional and molecular methods. Etiological agents were isolated from 564 (50.3%) specimens, and included 305 (54%) E coli, 157 (27.8%) Shigella species, and 102 (18%) from other genera of bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
53
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 24 publications
14
53
1
4
Order By: Relevance
“…For example, one large prospective surveillance study in the USA has indicated that EAEC strains are the most common causative agents of diarrhea in all age groups [1] . Other studies have shown that EAEC strains are among the important diarrheagenic strains isolated from Iranian patients [14][15][16][17][18] . On the other hand, treatment of the EAEC infections has become increasingly difficult due to the emergence of resistant pathogens [2] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, one large prospective surveillance study in the USA has indicated that EAEC strains are the most common causative agents of diarrhea in all age groups [1] . Other studies have shown that EAEC strains are among the important diarrheagenic strains isolated from Iranian patients [14][15][16][17][18] . On the other hand, treatment of the EAEC infections has become increasingly difficult due to the emergence of resistant pathogens [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate that multidrug resistant E. coli are widespread among the DEC strains and occurrence of resistant DEC could be because of environmental conditions, including transmission of resistant isolates from adults to children, or from animals to humans [38]. The main factors for dissemination of resistance genes are mobilizable plasmids, self-transmissible plasmids and conjugative transposons [39].…”
Section: Discussionmentioning
confidence: 99%
“…The disease remains a health problem challenge especially in developing countries [1][2][3]. The causative pathogens include a wide variety of microorganisms like bacteria, viruses and parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Altun ve Gür (2) çalışmamıza paralel olarak % 74.2 genel direnç oranı bulurlarken, S.sonnei için daha yüksek direnç oranı bildirmişlerdir. Ülkemizde ve yurt dışında yapı-lan bir çok çalışmada oldukça yüksek direnç oranları (% 55-92) verilmektedir (1,3,(11)(12)(13)(14)17,21) . Çalışmamızda son beş yılda elde edilen direnç verilerinin ilk beş yıla oranla yükseldiği görül-mektedir (Tablo 3).…”
Section: Introductionunclassified